Bilingual Education Programs in Primary Education: What Do Parents Think? - Martina Soledad Ramírez-Orduña; Daniel Rodríguez-Rodríguez; Francisco Javier Batista-Espinosa; Laura Barboyon Combey (Revista Colombiana de Educación)
Bilingual education programs are increasingly being implemented during mandatory schooling to meet to the educational and labor demands of a globalized world. For these programs to be successful, they must be implemented effectively and supported by all stakeholders. Therefore, the objective of this research is to determine parental opinions on bilingual (English-Spanish) programs used in schools in the monolingual Autonomous Community of Extremadura (Spain). Semi-structured interviews were conducted with 136 parents of students in the final stage of Elementary Education to gather their perceptions of bilingual education programs. Quantitative and qualitative analyses were conducted on the collected data, providing a comprehensive interpretation of family opinions. Bronfenbrenner's Ecological Theory was used to facilitate the interpretation of thematic categories from the qualitative data. The results show some positive opinions in thematic categories related to knowledge acquisition and the usefulness of the language. However, the majority of parents expressed concerns about teaching techniques, teacher training, students' emotions and excessive workload, and their own perceived difficulty in participating in their children's education. Additionally, positive opinions were mostly associated with the macrosystem of the social environment, while negative opinions were linked to the mesosystem of the teaching staff. The results suggest that parental opinions should be considered for the successful implementation of bilingual education projects.